327 - The Course and Predictors of Quality of Life in Nursing Home Residents with Young-onset Dementia. (October 2020) - Pu, Lihui; Bakker, Christian; Appelhof, Britt; Van Duinen-van den Ijssel, Jeannette C.L.; Zwijsen, Sandra A.; Teerenstra, Steven; Smalbrugge, Martin; Verhey, Frans R.J.; de Vugt, Marjolein E.; Zuidema, Sytse U.; Koopmans, Raymond T.C.M.
Abstract : Background: People with young-onset dementia (YOD) living in nursing homes may experience poor quality of life (QoL) due to advanced dementia, high prevalence of neuropsychiatric symptoms and psychotropic drug use. However, the course of QoL in institutionalized people with YOD and factors that predict this course are unclear. This knowledge could help health professionals identify appropriate interventions to improve QoL in YOD. Objective: To explore the course of QoL in institutionalized people with YOD and resident-related predictors of that course. Methods: Secondary analyses were conducted with longitudinal data from the Behavior and Evolution in Young-ONset Dementia (BEYOND)-II study. A total of 278 people with YOD were recruited from 13 YOD special care units in the Netherlands. QoL was measured by the proxy assessment of Quality of Life in Dementia (QUALIDEM) questionnaire at four assessments over 18 months. Independent variables included age, gender, dementia subtype, length of stay, dementia severity, neuropsychiatric symptoms and psychotropic drug use at baseline. Multilevel modeling adjusted for correlation within nursing homes and residents was used to determine the course and predictors of QoL. Results: The total QUALIDEM score (range: 0–111) decreased over 18 months with a statistically significant decline of 0.73 points per six months. A significant increase of QoL over time was seen in the subscales "Care relationship", "Positive self-image", and "Feeling at home". However, a significant decline was observed in the subscales "Positive affect", "Social relations", and "Something to do". Residents' course of QoL was positively associated with the baseline scores of the QoL, age and longer duration of stay; however, being male, having advanced dementia, Alzheimer's disease and high rates of neuropsychiatric symptoms at baseline were negatively associated with the course of QoL Conclusion: Longitudinal changes in QoL in residents with YOD were small over 18 months and QUALIDEM subscales showed multidirectional changes. The largest QoL decline in the subscale "Positive affect" suggests that interventions should be targeted to improve positive emotions, in particular for male residents with neuropsychiatric symptoms and advanced dementia.